Komunikasi Visual sebagai Penunjang Pengembangan Merek UMKM Berbasis Digital di Kelurahan Karangsari, Kecamatan Sukorejo, Kota Blitar - Desravi Putri, Aisyah; Illahi, M. Ridho; Ainurriyah, Ainurriyah; Setyo Budiwitjaksono, Gideon; Abuzar Zuhri, M. Fernanda (Universitas Gajah Putih, Indonesia, 2023)
As digital technology develops, branding activities increasingly refer to the use of social media and e-commerce platforms, so that public attention to the visual side is also increasing. Digital brand development with visualization according to the target market is needed as a long-term strategy. The object of the PKM activities in this journal is Rengginang Bu Anik, located in Karangsari Village, Blitar City. The method used consists of 3 stages, namely the identification of problems by filling out questionnaires and interviews. The second stage is the implementation stage by creating a logo, packaging stickers, product photos and promotional videos and creating an Instagram account. The last stage is maintenance by accepting criticism, suggestions and input on the results that have been obtained. This activity is carried out to increase public brand awareness of the brand of the chosen service object, so that the brand can compete with other similar businesses.